2020
DOI: 10.1080/20002297.2020.1808750
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic cooperativity between Porphyromonas gingivalis and Treponema denticola

Abstract: Background: Porphyromonas gingivalis and Treponema denticola are proteolytic periodontopathogens that co-localize in polymicrobial subgingival plaque biofilms, display in vitro growth symbiosis and synergistic virulence in animal models of disease. These symbioses are underpinned by a range of metabolic interactions including cooperative hydrolysis of glycine-containing peptides to produce free glycine, which T. denticola uses as a major energy and carbon source. Objective: To characterize the P. gingivalis ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…S-PRG filler also had an inhibitory effect on Streptococcus oralis and Streptococcus gordonii 33 , and may inhibit sugar metabolism by oral streptococci. In contrast, Porphyromonas gingivalis , a major Gram-negative periodontopathic bacterium, is unable to metabolize sugar and uses protease activity to degrade proteins as energy sources 34 , 35 . S-PRG filler can inhibit the protease activity of P. gingivalis 36 .…”
Section: Discussionmentioning
confidence: 99%
“…S-PRG filler also had an inhibitory effect on Streptococcus oralis and Streptococcus gordonii 33 , and may inhibit sugar metabolism by oral streptococci. In contrast, Porphyromonas gingivalis , a major Gram-negative periodontopathic bacterium, is unable to metabolize sugar and uses protease activity to degrade proteins as energy sources 34 , 35 . S-PRG filler can inhibit the protease activity of P. gingivalis 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we compared P. gingivalis gene expression in the 12 periodontitis samples to 122 transcriptomes of wild-type P. gingivalis collected during growth in experimental model systems (Table 2 and Dataset S2C). A total of 117 of these transcriptomes were from in vitro culture from 12 publications, mostly from growth in rich media under laboratory conditions (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Of these transcriptomes, 85 were from monoculture and 32 from pairwise coculture with either Streptococcus gordonii, Acinetobacter baumannii, or Candida albicans.…”
Section: The P Gingivalis In Situ Transcriptional Profile Clusters Withmentioning
confidence: 99%
“…They are involved in the formation of dental plaque and some species contribute to the development of caries [ 62 , 63 ]. Many of these are pathogens, such as the Porphyromonas gingivalis , which is an anaerobic Gram-negative bacterium that can cause various diseases such as periodontitis, abscesses, and endocarditis, and T. denticola , which is a Gram-negative, obligate anaerobic causing periodontitis [ 64 , 65 , 66 ]. Studies have shown that cotinine (a substance found in cigarette smoke) can interfere with P. gingivalis ability to bind and invade epithelial cells [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%